Rancang Bangun Buka Tutup Pintu Otomatis dengan Menggunakan Arduno UNO / MEGA 2560 - Fadil Rahman; Myson Myson; Fadli Eka Yandra (Universitas Batanghari Jambi, 2019)
The Arduino Board has been widely used as a prototyping device for both educational, research and commercial purposes. The ability of Arduino boards to be connected with electronic devices or gadgets such as Android operating system devices is getting more attention among researchers. By utilizing the various capabilities possessed by most Android operating system devices on the market today, the Arduino board will certainly have extraordinary intelligence. Some of the ways that Android devices can communicate with Arduino are via a Bluetooth shield, Wi-Fi shield, and also by serial communication. The idea that emerged was to utilize the ATMega328 microcontroller serial communication capability on the Arduino board. Serial data sent from an Android device is passed through an audio jack cable then connected to the Rx port on the Arduino board. In this Final Project will be designed and realized serial communication between the Android and Arduino platforms through audio channels with text input with the aim that Android can send text data through audio channels with audio cables. In testing the data speed utilizing the Arduino serial monitor it was found that the optimal speed was 19200bps. Whereas the maximum speed is 38400bps which can still be used for uniform serial data communication with an error of less than 5%. However, the maximum speed cannot be used for diverse data because the data error is more than 30%. The data cannot be read at speeds of 14400bps, 28800bps, speeds under 300bps and speeds above 57600bps.